2010
DOI: 10.2353/ajpath.2010.091287
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial-Specific Overexpression of Caveolin-1 Accelerates Atherosclerosis in Apolipoprotein E-Deficient Mice

Abstract: Caveolin-1 (Cav-1) is the major structural protein essential to the formation of the caveolae in endothelial cells. Genetic ablation of Cav-1 on an apolipoprotein E knockout background inhibits the progression of atherosclerosis, whereas re-expression of Cav-1 in the endothelium promotes lesion expansion. Although Cav-1-null mice are useful to delineate the importance of caveolae in atherosclerosis, there are additional problems that are difficult to dissect because loss of Cav-1 abolishes both the caveolae or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 27 publications
5
65
0
Order By: Relevance
“…Another key finding of our work stems from the observation that CavNOxin-induced NO upregulation was able to attenuate aortic and endothelial VCAM-1 expression, which correlated closely with the reduction in leukocyte/monocyte adhesion to the vascular wall and to cultured endothelial cells in diabetic and inflammatory (TNF-a) settings, lending credence to previous studies that demonstrated decreased leukocyte recruitment and VCAM-1 expression in Cav-1 KO tissues (38)(39)(40). Furthermore, increased eNOS activity has been associated with the downregulation of adhesion molecules, in particular VCAM-1 (19), and our data suggest that this can be achieved specifically through endogenous eNOS in a compensatory manner because hyperglycemia is a potent inducer of leukocyte-endothelial interactions (13,41).…”
Section: Discussionsupporting
confidence: 75%
“…Another key finding of our work stems from the observation that CavNOxin-induced NO upregulation was able to attenuate aortic and endothelial VCAM-1 expression, which correlated closely with the reduction in leukocyte/monocyte adhesion to the vascular wall and to cultured endothelial cells in diabetic and inflammatory (TNF-a) settings, lending credence to previous studies that demonstrated decreased leukocyte recruitment and VCAM-1 expression in Cav-1 KO tissues (38)(39)(40). Furthermore, increased eNOS activity has been associated with the downregulation of adhesion molecules, in particular VCAM-1 (19), and our data suggest that this can be achieved specifically through endogenous eNOS in a compensatory manner because hyperglycemia is a potent inducer of leukocyte-endothelial interactions (13,41).…”
Section: Discussionsupporting
confidence: 75%
“…Less LDL penetration and greater NO production was seen in Cav-1 Ϫ/Ϫ mice (522). Endothelial-specific overexpression increased atherosclerosis (521). Even greater reduction in atherosclerosis seen in a more recent study (477).…”
Section: Calcium Signaling Ion Channels and Weibel-palade Body Exocmentioning
confidence: 92%
“…In their study published in the current issue of The American Journal of Pathology, Ferná ndez-Hernando et al 17 have demonstrated the important if not essential function of caveolin-1 in the development of atherosclerosis. Their data confirmed previous findings they had obtained using caveolin-1-deficient mice that were bred with mice overexpressing caveolin-1 specifically in endothelial cells.…”
Section: An Essential Role For Endothelial Caveolin-1 In the Developmmentioning
confidence: 97%